A new reference grammar of modern Spanish - Butt, John 1943-; Benjamin, Carmen; Rodrâiguez, Antonia Moreira (Routledge Reference Grammars, 2019)
"A New Reference Grammar of Modern Spanish is a comprehensive, cohesive and clear guide to the forms and structures of Spanish as it is written and spoken today in Spain and Latin America. It includes clear descriptions of all the main grammatical phenomena of Spanish, and their use, illustrated by numerous examples of contemporary Spanish, both Peninsular and Latin American, formal and informal. Fully revised and updated, the sixth edition is even more relevant to students and teachers of Spanish. The sixth edition includes: - new chapters, providing more detail and examples of key areas of Spanish grammar - an increased number of Mexican examples to reflect the growing interest in this country's variety of Spanish - new information for readers studying Spanish and French together - a glossary of grammatical terms including Spanish translations of Spanish terms The combination of reference grammar and manual of current usage is invaluable for learners at level B2 - C2 of the Common European Framework for Languages, and Intermediate High - Advanced High on the ACTFL proficiency scales"-- Provided by publisher.